PERENCANAAN PENGELOLAAN SARANA DAN PRASARANA PERPUSTAKAAN UNTUK MENINGKATKAN MINAT BACA SISWA DI SDN 03 SERUA - Siti Nazmiyah; Rahmi Fatma; Munjiyah Munjiyah; Nabila Nadiva Al-Ihsan (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to examine the planning of library facility and infrastructure management in increasing student reading interest at Serua 03 Public Elementary School. Reading interest is a crucial aspect in developing elementary school student literacy, but it still faces various obstacles, one of which is the suboptimal management of school literacy facilities. This study used a qualitative approach with descriptive methods. The research subjects included the principal and students, and data collection techniques included observation, interviews, and documentation studies. The data obtained were analyzed descriptively to describe the actual condition of library facility and infrastructure management. The results indicate that the planning of library facility and infrastructure management at Serua 03 Public Elementary School is not yet fully optimal, as evidenced by low library utilization by students, limited spatial planning, and a lack of innovation in literacy facility management. However, gradual planning efforts, including needs analysis, library reorganization, and facility maintenance, have shown a positive impact on increasing student interest in reading. The novelty of this study lies in strengthening the role of facility and infrastructure management planning as a school managerial strategy in fostering elementary school students' reading interest. This research is expected to serve as a reference for schools in developing effective and sustainable literacy facility management.